Macrophage Activation Syndrome as Initial Presentation of Systemic Lupus Erythematosus - Say-Tin Yeap; Jiunn-Ming Sheen; Ho-Chang Kuo; Kao-Pin Hwang; Kuender D. Yang; Hong-Ren Yu (Elsevier, 2008)
Macrophage activation syndrome (MAS) is known to be a severe and potentially life-threatening complication of rheumatic disorder, especially systemic juvenile rheumatoid arthritis. It is very rare for MAS to be an initial presentation of systemic lupus erythematosus (SLE). Here, we report a 14-year-old girl in whom MAS developed as an initial presentation of SLE. With early diagnosis and administration of cyclosporine A, she had a fair outcome. Further testing showed positive anti-dsDNA about 8 months later.